Egypt visual sourcebook : for artists, architects, and designers - Hewitt, Jim (American University in Cairo Press, 2011)
This unique visual reference guide will be an invaluable resource to professional designers--from architects to illustrators, production designers, art directors, decorators, film concept artists, sculptors, and painters. It utilizes color photographs to illustrate a wide range of locations and styles of architecture throughout Egypt, particularly highlighting architectural elements that may be incorporated into a variety of designs and styles including arches, doorways, windows, balconies, wall finishes, and more. Photographic plates of modern and ancient Egypt, showing markets, buildings, temples, tombs, and daily life are cross-referenced with enlarged details and grouped for functional comparisons to cater to the various approaches a designer may take from conception to completion. With some 1,000 color illustrations, thorough referencing, and detailed observation, this book will serve a very specific need while also appealing to a wider audience as a visual celebration of many aspects of Egypt, familiar and unfamiliar.--From publisher description.